What a way to make a living. - Dowling, Emma (New Humanist)
The article offers information on the impact of work on mental health. It mentions that identifications with work have come to characterize many people's lives, whether they have different jobs over the course of their lifetime. It also mentions several books of philosopher Franco "Bifo" Berardi including "The Soul At Work," "Precarious Rhapsody" and "After the Future."